Physiotherapists' experiences of activity pacing with people with chronic musculoskeletal pain: an interpretative phenomenological analysis. - Scott-Dempster, C; Toye, F; Truman, J; Barker, K (Informa Healthcare, 2014)
PURPOSE: Activity pacing is a strategy used by physiotherapists treating people with chronic pain. Questions as to the usefulness of activity pacing with people with chronic pain have been raised clinically and in research. This study explores physiotherapists' experiences of using activity pacing with people with chronic musculoskeletal pain. METHOD: We interviewed six physiotherapists and used the methods of Interpretative Phenomenological Analysis (IPA) to explore the meaning of pacing. RESULTS: We identified three master themes. First, activity pacing was perceived as part of a process whereby patients came to realize that change is possible, and that life could be different. Second, in order to use activity pacing effectively the physiotherapist needs to shift from a "fix it" to a "sit with" approach to the treatment. Third physiotherapists described how they used many combined therapeutic approaches in managing chronic pain. CONCLUSIONS: This study increases our understanding of activity pacing and will help to make the best use of activity pacing in clinical practice, and optimize outcomes for the patients. These findings suggest that physiotherapists need to develop reflective listening skills, and use an experiential learning approach to facilitate activity pacing.